The Affect of Covid-19 Pandemic Anxiety on Breast Milk Ejection of Postpartum Mother in Pmb Hj. Faridatul Ampera - Puriastuti, Alifia Candra; Yulianita, Esti Dwi; Saputri , Poppy Farantia (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
COVID-19 pandemic has made postpartum mothers experience anxiety from mild to fear of crowds and lock themselves at home. So that it affects the expenditure of postpartum mother's milk, because the increase in cortisol makes the hormone oxytocin inhibition in its secretion so that the release of breast milk is inhibited. Knowing the effect of the anxiety of the Covid-19 pandemic on the release of postpartum mother's milk at the Independent Practice Midwife Hj. Faridatul Ampera Performance. This type of research is an analytic survey using a cross sectional design. It is recommended that pregnant women always think positively and seek information about health, especially Covid-19 or do relaxation so that they are not anxious.